Gerenciamento de energia elétrica para otimizar a qualidade e a eficiência energética de grandes consumidores - Cruz, Roberto Ribeiro de Azevedo (2014)
This paper presents the management of power system of a major consumer, with the objective of minimizing cost and waste of electric energy, as well as providing controling of the behavior of its system of distribution of electric energy, causing the consumer unit to be able to monitorise the energy received through the dealership and delivered to their users, seeking to attain good levels in quality and energy efficiency. The work was developed in a large consumer UFPB CAMPUS - I, through the analysis of information regarding its energy efficiency, and system management using electric power management equipment and techniques to better control the quality and efficiency desired. The results obtained with the management show details of the reduction in the monthly bill of the unit analyzed with the elimination of fines caused by low power factor, improvements in hiring demands and regarding the continuity of energy supply. Measures and solutions adopted in this study can be applied to other consumers with all the conditions to reach the expected results, respecting their particularities and their productive activities